Optimized Industrial Automation Network for Efficient Productivity Using Quality of Service Policy Mechanism (QPM) - Ifeyinwa Faith Ogbodo, Emmanuel Utochukwu Ogbodo & (Covenant Journal of Informatics and Communication Technology, 2019)
In this paper, the complexity of industrial automation network when compared to the traditional IT corporate organization network or campus network, was first described. The challenges and components of industrial automation network have been highlighted. Hence, in order to overcome the challenges in the industrial automation network, the network was optimized by incorporating Quality of Service (QoS) Policy Mechanism (QPM) model in the network design. Existing mechanisms such as transmission control protocol (TCP) to deal with these problems, and the limitations of relying only on TCP were then discussed. The potential to improve the industrial automation network in the perspective of industrial internet of things (IIoT) has been reported in this paper as a further investigation in the future works. Simulation results were presented which showed that the optimized industrial automation network using QoS Policy Mechanism model gives higher performance throughput than the congestion control algorithm of the conventional TCP and the traditional network.